Development of a CLIS (Children Learning in Science) Model Using Canva to Enhance Primary School Pupils’ Science Literacy and Collaboration Skills - Kartini, Kartini (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This research focuses on the development of the ModelCLIS (Children Learning In Science) using the Canva application to address the problem of low scientific literacy and student collaboration among fifth-grade elementary school students. In the context of adapting education to technological advances in the eraSociety 5.0, constructive and adaptive learning model innovation becomes important. ModelCLIS (Children Learning In Science), which is based on constructivism and has ten systematic stages, was chosen to build students' conceptual understanding. Integration with Canva, a graphic design platformon line, aims to create visual and interactive learning media. This research adopts the methodResearch and Development (R&D), adapting the Borg & Gall (1983) model. The research subjects were 30 students of SDN 3 Selaawi for a limited trial of the teaching device. A broad trial was conducted at SDN 2 Pasawahan with 33 and an operational trial at SDN 1 Selaawi with 58. The results of expert validation showed that the developed learning device met the criteria.worthywith an average result of 91.52%. The effectiveness test was conducted using a randomized controlled design.pretest-posttestto measure the increase in scientific literacy. A significant increase was found in students' scientific literacy skills, where the average score rose from54.17%onpretestbecome80.83%onposttest. Testpaired samples t-testshows a significance value of 0.001 (Sig.(2-tailed) ≤ 0.05), while the collaboration capability shows a very good improvement. So it can be proven that the development of the modelCLIS (Children Learning In Science) Canva's assistance is effective in improving the scientific literacy and collaboration skills of V grade elementary school students.